The Moderating Role by Locus of Control Bridging Financial Knowledge of Financial Management Behaviour - Heryandya, Dinandara Aliya Rahma; Muhadjir Anwar (International Journal of Economics (IJEC), 2024)
The ease of access to needs and desires has led to the emergence of wasteful behaviour in society in this modern era. Therefore, financial knowledge is crucial in making daily financial decisions or managing businesses. Financialknowledge can potentially enhance the quality of life through improved decision-making. This study aims to explore how locus of control affects the connection between financial knowledge and financial management behaviour as a moderating variable using a quantitative research method with primary data. The research population consists of TikTok Shop customers in Surabaya City. Data Analysis utilises Partial Least Square (PLS) with tests on the outer model, inner model, and hypothesis. Outputs of this search imply that financial knowledge and locus of control significantly as well as positively influence financial management behaviour. Still, locus of control variable doesn’t possess capacity to moderate the correlation among financial knowledge and financial management behaviour.